Housekeeping management - Samson-Roldan, Amelia; Crespo, Amelia Malapitan (Paranaque City, Philippines : AR Skills Development & Management Services, 2003)
The book is an ideal reference for people who wish to master the art of professional housekeeping and make it a daily habit.
Housekeeping organization -- Cleaning supplies and procedures -- Floor care, cleaning and maintenance -- Guestroom cleaning, care and maintenance -- Linen and laundry service -- Sanitation in housekeeping operations -- Safety and security in housekeeping -- Managing and monitoring the housekeeping job
Keywords: HOTEL HOUSEKEEPING -- MANAGEMENT